2016
DOI: 10.1371/journal.pntd.0004568
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Antivenoms for Snakebite Envenoming in 16 Countries in West Africa

Abstract: BackgroundSnakebite poisoning is a significant medical problem in agricultural societies in Sub Saharan Africa. Antivenom (AV) is the standard treatment, and we assessed the cost-effectiveness of making it available in 16 countries in West Africa.MethodsWe determined the cost-effectiveness of AV based on a decision-tree model from a public payer perspective. Specific AVs included in the model were Antivipmyn, FAV Afrique, EchiTab-G and EchiTab-Plus. We derived inputs from the literature which included: type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 49 publications
5
34
0
2
Order By: Relevance
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We consistently found that young to middle-aged men (age group = 15-44 years) were most at risk of snakebites, corroborating similar findings from Ghana [22, 23, 24], other parts of West Africa [15, 25, 26, 27, 44, 46, 47] and Africa in general [30, 34, 48, 49, 50]. Adolescent and young men in their twenties are among the most active and adventurous, albeit least cautious, section of rural African people [24, 27, 44, 51].…”
Section: Discussionsupporting
confidence: 87%
“…amputations) or death, even if such treatment is administered correctly [22, 42, 44, 45]. It is therefore important to ascertain the extent of both untreated and delayed treatments in order to address these clinical and epidemiological shortcomings in the management of snakebites in remote rural parts of Ghana and sub-Saharan Africa [2, 13, 15, 40, 42]. We hope our snakebite data analyses from the Savelugu-Nanton District, a typical northern savanna community in Ghana, will aid in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Partnership with academia, other frameworks of social cooperation and industry already in possession of valuable pre-clinical and toxicological data, especially for off-patent compounds could speed development of these and other potential therapeutics for saving lives. Similarly, if these field-treatments can reduce healthcare costs related to snakebite even small reductions in the need for ICU and operative care, which even with no reduction in antivenom use, would be tremendously cost saving [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only two cost-effectiveness analyses on snakebite treatments were identified at the time of our study. 30 , 31 These studies have determined that antivenom (administered alongside supportive care) is cost-effective in a variety of West African settings. Our study seeks to answer the following additional question, “For what cost and efficacy values would a combination antivenom/adjunct-based treatment strategy for venomous snakebites be cost-effective when compared with using antivenom alone?”…”
Section: Introductionmentioning
confidence: 99%